Covid-19 Pandemic and the Fiscal Strategy of the International Monetary Fund: Towards New Directions in the Global Political Economy? - Amoretti, Francesco; Cozzolino, Adriano; Giannone, Diego (PARTECIPAZIONE E CONFLITTO, 2021)
This article seeks to contribute to the analyses of the impact of the Covid-19 on the global political economy. It does so through a qualitative content analysis of the key policy documents published by the International Monetary Fund (IMF) since the outbreak of the pandemic crisis. The IMF has been, historically, one of the main designers of international macroeconomic governance. The paper focuses on fiscal policy, which retains a central place in the strategy of the IMF to deal with the pandemic and especially for the post-pandemic recovery phase. The analysis of the documents of the IMF contributes (i) to appreciate the interpretation of the nature of the pandemic crisis through the lenses of a prominent international financial institution, (ii) to explore the policy strategy outlined to deal with the pandemic emergency, (iii) to assess possible changes at the level of policy, and accordingly, future directions in global political economy. Evidence suggests that fiscal stimulus, public investment and planning will likely have a prominent position in the future directions of the IMF policy advice.